2023
DOI: 10.1128/spectrum.01206-23
|View full text |Cite
|
Sign up to set email alerts
|

Construction and functional verification of size-reduced plasmids based on TMP resistance gene dfrB10

Chun-cao Li,
Rui Hu,
Xiu-min Hua
et al.

Abstract: Antibiotic resistance screening is crucial in the construction of recombinant plasmids. The dfrB10 gene, a short-size trimethoprim (TMP)-resistance type B dihydrofolate reductase gene, is a promising antibiotic drug screening marker for plasmid construction in molecular genetic research. Currently, available plasmid backbones (without the resistance gene) were amplified using PCR, and then we ligated these products with dfrB10 gene fragments via homologous recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…We believed that we had reached the absolute minimal possible vector in the generation of the 1185 bp pICOz vector [3]. However, the recently published pUdOs series of plasmids and another series of plasmids utilizing the tiny trimethoprim resistance genes [4], [5] showed that there are further opportunities for miniaturization. Inspired by this, we set out to investigate how much further we could miniaturize our previous pICOz cloning plasmid.…”
Section: Introductionmentioning
confidence: 99%
“…We believed that we had reached the absolute minimal possible vector in the generation of the 1185 bp pICOz vector [3]. However, the recently published pUdOs series of plasmids and another series of plasmids utilizing the tiny trimethoprim resistance genes [4], [5] showed that there are further opportunities for miniaturization. Inspired by this, we set out to investigate how much further we could miniaturize our previous pICOz cloning plasmid.…”
Section: Introductionmentioning
confidence: 99%